The effects of bioactive components from the rhizome of gastrodia elata blume (Tianma) on the characteristics of Parkinson’s disease - Lu, Changcheng; Qu, Shuhui; Zhong, Zhangfeng; Luo, Hua; Lei, Si San; Zhong, Hai-Jing; Su, Huanxing; Wang, Yitao; Chong, Cheong-Meng (Frontiers in Pharmacology, 2022)
Parkinson’s disease (PD) is an age-related chronic neurodegenerative disease caused by the death and degeneration of dopaminergic neurons in the substantia nigra of the midbrain. The decrease of the neurotransmitter dopamine in the patient's brain leads to various motor symptoms. PD drugs mainly enhance dopamine levels but cannot prevent or slow down the loss of dopaminergic neurons. In addition, they exhibit significant side effects and addiction issues during long-term use. Therefore, it is particularly urgent to develop novel drugs that have fewer side effects, can improve PD symptoms, and prevent the death of dopaminergic neurons. The rhizome of Gastrodia elata Blume (Tianma) is a well-known medicinal herb and has long been used as a treatment of nervous system-related diseases in China. Several clinical studies showed that formula comprising Tianma could be used as an add-on therapy for PD patients. Pharmacological studies indicated that Tianma and its bioactive components can reduce the death of dopaminergic neurons, α-synuclein accumulation, and neuroinflammation in various PD models. In this review, we briefly summarize studies regarding the effects of Tianma and its bioactive components’ effects on major PD features and explore the potential use of Tianma components for the treatment of PD.